PENGARUH SPOT RATES DAN FORWARD RATES TERHADAP FUTURES RATES PADA HARGA KOMODITAS OLEIN DI BBJ 2015-2017 - Posma Sariguna Johnson Kennedy; Melina Geni Putri Sinaga (Universitas Muhammadiyah Metro Lampung, 2019)
The economic crisis that has happened shows that the agribusiness sector can survive, so that the development of the agribusiness sector is one of the priorities. Olein is one of the agribusiness commodities that are traded through futures contracts. The purpose of this study is to see the effect of spot and forward rates on futures rates on olein commodities on the Bursa Berjangka Jakarta (JFX) for the 2015-2017 period. The research method used is a quantitative method by testing the hypothesis whether the independent variables affect the dependent variable, that whether the prediction of futures rates can be made using the variable of the forward rates and spot rates. The method is done by observing the price data published at Bappebti and JFX. The data used are secondary data, obtained from bappebti.co.id and jfx.co.id. Testing is done after the data has passed the classical assumption test. The results of this study indicate that forward rates do not affect futures rates, while spot rates affect futures rates. Keywords: Forward Rates, Spot Rates, Future Rates, Olein Commodity, Jakarta Futures Exchange